TANGGUNG JAWAB NEGARA DALAM IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH TERHADAP AKTIVITAS EKONOMI PASAR: PERSPEKTIF HUKUM LINGKUNGAN DAN PEMBANGUNAN BERKELANJUTAN - Lengkong, Mario Randy; Lase, Melfina; Damanik, Paulisa Gloria Br; Sembiring, Hatita Br; Tuanakotta, Hendra Joseph (Gapenas Publisher, 2025)
This study analyzes state responsibility in implementing local government policies related to economic activities in traditional markets from an environmental law perspective. The background of this research lies in the dilemma between promoting people’s economic development and the state’s constitutional duty to protect environmental sustainability as mandated by Article 33(3) and Article 28H(1) of the 1945 Constitution of the Republic of Indonesia. The objective of this study is to assess how the principle of state responsibility is embodied through local government policies in managing sustainable market environments. Using a normative juridical method with statutory and conceptual approaches, the research examines primary legal sources, including Law No. 32 of 2009 on Environmental Protection and Management, Law No. 23 of 2014 on Local Government, and Law No. 18 of 2008 on Waste Management. The findings reveal that state responsibility is hierarchical and decentralized through the authority of local governments; however, implementation remains constrained by weak institutional coordination, limited budgets, and low environmental awareness among market participants. The study also finds that legal instruments such as environmental permits, Strategic Environmental Assessments, and Environmental Impact Analyses are not yet effectively applied at the traditional market level. In conclusion, strengthening local regulations, enhancing institutional capacity, and promoting community participation are essential steps to ensure that state responsibility is effectively realized in achieving economically and ecologically sustainable traditional markets